Lightweight cement pastes with hollow glass microspheres: Analytical estimation of elastic parameters - Martín, Christian Marcelo (2023)
An analytical model is presented for estimation of the elastic parameters of lightweight cement pastes with hollow glass microspheres (HGMS). The microspheres consist of a siliceous spherical outer shell filled with gas, providing a density modification agent for the cement paste. The obtained lightweight cement paste is used for cementing deep wells where it is necessary to guarantee the integrity of the cement sheath to avoid fluid migration, contain the rock mass and protect the casing. The proposed micromechanical model, compared to other alternatives, results in an easy-to-use approach for obtaining an estimation of the elastic parameters of the HGMS lightweight cement. The elastic parameters are necessary for the design of the cement sheath and the analysis of its performances. The model input parameters are the elastic parameters of the cement matrix and the microspheres, as well as microspheres dimensions and volume fraction, which are easy to obtain. The model predictions are compared to experimentally evaluated elastic parameters of lightweight cement pastes. A good compatibility between predictions and experimental data is obtained, even when assuming a perfectly bounded interface between the microspheres and the cement matrix.The model also permits to take into account an imperfect interface between the microspheres and the cement matrix improving the model predictions with respect to the experimental results. The model presents an engineering tool to design lightweight cement slurries with hollow microspheres and to estimate their mechanical contribution to a cement sheath for drilling operations.